1968
DOI: 10.1113/jphysiol.1968.sp008574
|View full text |Cite
|
Sign up to set email alerts
|

Application of fourier analysis to the visibility of gratings

Abstract: SUMMARY1. The contrast thresholds of a variety of grating patterns have been measured over a wide range of spatial frequencies.2. Contrast thresholds for the detection of gratings whose luminance profiles are sine, square, rectangular or saw-tooth waves can be simply related using Fourier theory.3. Over a wide range of spatial frequencies the contrast threshold of a grating is determined only by the amplitude of the fundamental Fourier component of its wave form.4. Gratings of complex wave form cannot be disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

75
1,299
5
50

Year Published

1971
1971
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,783 publications
(1,429 citation statements)
references
References 7 publications
(12 reference statements)
75
1,299
5
50
Order By: Relevance
“…We can thus legitimately make a different and potentially interesting comparison between the effects of broad-and narrowband noise when they have been equated for noise power per cycle per degree. This comparison is interesting because it allows us to estimate the effective bandwidth of the spatial frequency channels hypothesized by Campbell and Robson (1968). Provided we assume that the ratio of signal to noise power within a channel is the determining factor in detection, the channel widths at each frequency are given simply as the ratio of the square of the threshold contrasts in the broad-and narrowband noise conditions.…”
Section: Resultsmentioning
confidence: 99%
“…We can thus legitimately make a different and potentially interesting comparison between the effects of broad-and narrowband noise when they have been equated for noise power per cycle per degree. This comparison is interesting because it allows us to estimate the effective bandwidth of the spatial frequency channels hypothesized by Campbell and Robson (1968). Provided we assume that the ratio of signal to noise power within a channel is the determining factor in detection, the channel widths at each frequency are given simply as the ratio of the square of the threshold contrasts in the broad-and narrowband noise conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The fundamental frequency of this grating was in the low-frequency region of the contrast sensitivity function where sensitivity to squarewaves exceeds that to sinewaves by more than 4/n (cf. Campbell and Robson, 1968). Thus, at threshold the fundamental component of the squarewave remains below its detection threshold, so that only the higher harmonics contribute to detection.…”
Section: Rationale For the Present Experimentsmentioning
confidence: 99%
“…) rather than the fundamental frequency (f) determines threshold for the low-frequency squarewave grating. Campbell and Robson (1968) further showed that a single-channel system, represented by a single contrast sensitivity function, could not account for the difference between the sensitivity to sinewave and squarewave gratings at low spatial frequencies. They, therefore, suggested the existence of multiple channels, each tuned to a different spatial frequency, acting independently (see also, Sachs et al, 1971;Graham and Nachmias, 1971).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observations of Campbell & Robson (1968) introduced a concept of human visual processing which has proved fertile ground for much subsequent experimental investigation. Snellen letter recognition, for example, is considered to be founded upon the ability of the visual system to detect and code the contrast components of the range of spatial frequencies comprising the test optotype subsequent to filtering by the CSF.…”
Section: Discussionmentioning
confidence: 99%